KERAGAMAN SERANGGA PADA Oryza sativa L. DI KECAMATAN PILANGKENCENG DAN KECAMATAN KARE KABUPATEN MADIUN - Eni Nur Fadilah; Cicilia Novi Primiani (UNIVERSITAS PGRI MADIUN, 2014)
The research aims to identify the insects in rice plants in the district Pilangkenceng and Kare Madiun. Research method using qualitative descriptive and in accordance with what is on the field. Data were collected by observation. Insects captured in two ways: directly and using flay arrest of the net. The results showed that the insects found in rice plant in the district of Pilangkenceng order Orthoptera, Hemiptera, Odonata, Hymenoptera, Lepidoptera, Coleoptera and Diptera. Insects found in the District of Kare consists of the Order Orthoptera, Odonata, Lepidoptera, Coleoptera and Homoptera.